Atypical presentation of adrenal pheochromocytoma with central tumour necrosis in a paediatric patient: a case report - Maliki, Aminnur H.; Sidi, Nurazim; Wan Ali, Sharifah A.; Ali, Adibah (International Surgery Journal, 2022)
Pheochromocytoma is a rare catecholamine producing neuroendocrine tumour in children. It is usually presented with a triad of palpitation, headache, and diaphoresis. It is one of the causes of secondary hypertension in children. We report a case of a girl who presented with atypical symptoms of pheochromocytoma. A 10-year-old girl who presented with chest discomfort, shortness of breath and labile blood pressure. A young hypertension workup revealed a non-functioning left adrenal mass, making the dilemma in the initial clinical diagnosis. Confirmative diagnosis of pheochromocytoma was obtained via histopathological examination of the specimen through laparoscopic left adrenalectomy, which offered both diagnostic and therapeutic values. She was successfully treated via minimally access surgery. Diagnosing a pheochromocytoma in paediatric age group can be challenging due to its scarcity and possible atypical initial presentation. It requires high index of suspicion for a timely diagnosis and prompt treatment.